Teachers’ Professional Collaboration: Current Status, Barriers and Suggestions - Kürşad Yılmaz (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
There are few studies examining teachers’ attitudes towards collaboration and the situation in practice in a centralized education system. In this research, teachers’ attitudes towards professional collaboration and collaboration behaviours in Turkey were examined via mixed method research. The data were collected from 274 teachers for the quantitative part and the qualitative part consisted of 53 teachers as participants. According to the results, teachers have a positive attitude towards collaboration. However, these positive attitudes are reflected in behaviours at a lower level. When it comes to professional collaboration, teachers immediately think of the work which is carried out with teachers in the same branch. With the effect of the centralized system, teachers in the study defined official meetings or working groups as collaboration activities. They mostly collaborate on the issues such as ‘educational activities and personality development of students’. They also indicated informal conversations and daily conversations as collaboration. According to the teachers, professional collaboration studies make important contributions to the school climate in general, increase teachers’ job satisfaction, motivation, performance and their sense of belonging. Moreover, teachers also stated that these studies improve the problem-solving skills of the school and they are beneficial to the students as well.